PENGARUH KINERJA KOPERASI SIMPAN PINJAM PKPRI SERANG BANTEN TERHADAP KESEJAHTERAAN ANGGOTA/KARYAWAN: PENGARUH KINERJA KOPERASI SIMPAN PINJAM PKPRI SERANG BANTEN TERHADAP KESEJAHTERAAN ANGGOTA/KARYAWAN (Faletehan Jurnal Ekonomi dan Bisnis, 2022)
This research was carried out on employees at Credit Unions PKPRI Serang Banten as relatedto the subject of this study on the Influence of Assessment Work Welfare Member / EmployeeCredit Unions PKPRI Serang Banten), by because it is in support of the discussion in this study,the data is needed valid-data associated with the two variables above. Assessment Workbecomes variable X (independent) and Promotion Position in deskrifsikan as a variable Y(dependent). Based on the data obtained, the level of agreement on the implementation ofAssessment of employees at Credit Unions PKPRI Serang Banten positive effect on welfareMember / Employee. Thus the appraisal of Credit Unions PKPRI Serang Banten significanteffect on Welfare Member / Employee so as to motivate employees to work harder in order toget a good assessment. This shows that the employee could not agree on the indicators workassessment.